A Survey on the Development of Real-Time Overcurrent Relay Coordination Using an Optimization Algorithm - Kamble, Vijaykumar S.; Khampariya, Prabodh; Kalage, Amol A. (International Journal of Intelligent Systems and Applications in Engineering, 2023)
The current work is a survey on the development of real-time overcurrent relay coordination utilizing an optimization approach. Overcurrent relays are a safeguard commonly used in transmission and distribution networks owing to their low cost. Depending on the operating conditions and the location of the faults, load or fault currents in a mesh system may loop in or out of the protective zone of the overcurrent relay. As a result, directional overcurrent relays are employed to determine whether the fault is inside or outside the protective zone. The goal of overcurrent relay coordination is to find settings that minimize operating time for failures within the protective zone. In addition to this it provides scheduled backup for relays in neighbouring zones that has been pre-specified. As an outcome, the highest possible fault current observed by the relay must be greater than maximum fault currents in its protective zone detected in zones close by.